High-heat-insulation explosion-proof film as well as preparation method and application thereof
Through the combination of solized polyurethane, composite glass microsphere powder and nanocellulose fibers, a film with high heat insulation and excellent explosion-proof performance is formed, which solves the shortcomings of polyurethane films in heat insulation and explosion-proof, and realizes the high-temperature environment Effective heat insulation and explosion-proof effect under explosion impact.
Patent Information
- Application Number
- CN202411341542.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
Polyurethane films have weak performance in terms of heat insulation and explosion protection, especially in high temperature environments, and are limited in heat resistance and cannot provide sufficient protection to prevent glass fragments from splashing or other explosive damage.
Solized polyurethane, composite glass microsphere powder and nanocellulose filaments are used to form films with high heat insulation, excellent mechanical properties and explosion-proof properties through the action of compatibilizers and curing agents. Specific steps include ultrasonic dispersion, stirring and standing to prepare solized polyurethane and composite glass microsphere powder, followed by mixing and casting onto a PVC sheet to dry the film.
It significantly improves the thermal insulation, mechanical strength and explosion-proof performance of the film, can effectively insulate heat in high temperature environments and prevent glass from breaking during explosion impact, and the tensile strength reaches more than 38MPa.
Smart Images

Figure BDA0005059841340000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of films, and in particular to a highly heat-insulating and explosion-proof film and a preparation method and application thereof. Background Art
[0002] With the advancement of science and technology and people's increasing demand for safety and comfort, film materials are increasingly used in various fields, especially in the automotive, construction and aerospace industries, where performance requirements are more stringent. The advantages of polyurethane film are: polyurethane film has high tensile strength and wear resistance, and can withstand a certain degree of physical stress; polyurethane film has good electrical insulation properties and is suitable for the preparation of electronic products and insulating materials.
[0003] However, in terms of heat insulation and explosion protection, the performance of polyurethane film is relatively weak. Although polyurethane film has a certain impact resistance, it does not have professional explosion-proof functions. When encountering strong impact or explosion, polyurethane film may not provide sufficient protection to prevent glass fragments from flying or other potential explosion injuries. In addition, the thermal insulation performance of polyurethane film is also average, especially in high temperature environments, its heat resistance is limited, which limits its thermal insulation application in high temperature environments.
[0004] To this end, the present application provides a highly heat-insulating and explosion-proof film and a preparation method and application thereof. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the high thermal insulation and explosion-proof film described in this application is formed by using sol-gelled polyurethane, composite glass microsphere powder, nanocellulose fibrils and other raw materials under the action of a compatibilizer and a curing agent to form a film with excellent thermal insulation, mechanical properties and explosion-proof properties.
[0006] The technical solution provided by this application is:
[0007] The first object of the present application is to provide a high heat-insulating and explosion-proof film, comprising the following raw materials in parts by weight:
[0008] 50-60 parts of sol-gelled polyurethane, 5-10 parts of composite glass microsphere powder, 10-15 parts of compatibilizer, 1.0-1.5 parts of curing agent, 3-5 parts of nanocellulose fibrils, and 3-5 parts of dispersant;
[0009] The preparation method of the sol-formed polyurethane comprises the following steps:
[0010] Ammonia water and aqueous polyurethane are sequentially added to anhydrous ethanol, ultrasonically dispersed at room temperature, and then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane are added, stirred at room temperature for 5-6 hours, and then allowed to stand for 24-30 hours to obtain a sol-formed polyurethane;
[0011] The preparation method of the composite glass microsphere powder comprises the following steps:
[0012] Ammonia water and hollow glass microspheres are sequentially added to anhydrous ethanol, and ultrasonically dispersed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane are added to the suspension, stirred at room temperature for 8-9 hours, and then allowed to stand for 24-30 hours; and dried at 50-60° C. to obtain composite glass microsphere powder.
[0013] In some embodiments, the aqueous polyurethane has a viscosity of 50-500 mPa·S.
[0014] In some embodiments, the hollow glass microspheres have a particle size of 1-10 μm.
[0015] In some embodiments, the nanocellulose fibrils have a diameter of 10-20 nm and a length of 100-200 nm.
[0016] In some embodiments, the compatibilizer is a maleic anhydride grafted compatibilizer.
[0017] In some embodiments, the curing agent is diethylenetriamine or triethylenetetramine.
[0018] In some embodiments, in the preparation method of the sol-gel polyurethane, the volume ratio of waterborne polyurethane, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:10-15:1;
[0019] In the preparation method of composite glass microsphere powder, hollow glass microspheres, tetraethyl silicate,
[0020] The feed ratio of dodecyltriethoxysilane = 1 g: (35-40) mL: (3-5) mL.
[0021] In some embodiments, the dispersant is sodium polyacrylate.
[0022] The second object of the present application is to provide a method for preparing the above-mentioned film, comprising the following steps:
[0023] S1. Preparation of sol-gelled polyurethane
[0024] Ammonia water and aqueous polyurethane are sequentially added to anhydrous ethanol, ultrasonically dispersed at room temperature, and then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane are added, stirred at room temperature for 5-6 hours, and then allowed to stand for 24-30 hours to obtain a sol-formed polyurethane;
[0025] S2. Preparation of composite glass microsphere powder
[0026] Adding ammonia water and hollow glass microspheres to anhydrous ethanol in sequence, and performing ultrasonic dispersion at room temperature to obtain a suspension; adding tetraethyl silicate and dodecyltriethoxysilane to the suspension, stirring at room temperature for 8-9 hours, and then standing for 24-30 hours; drying at 50-60° C. to obtain composite glass microsphere powder;
[0027] S3. Preparation of mixed liquid
[0028] According to the weight composition of the high heat insulation and explosion-proof film, corresponding weight portions of raw materials are prepared; the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol are fully mixed; and then the sol-formed polyurethane and curing agent are added to obtain a mixed liquid;
[0029] S4. Film forming process
[0030] The mixed liquid is cast onto a PVC sheet; and dried at 40-60°C to obtain a highly heat-insulating and explosion-proof film.
[0031] The third purpose of the present application is to provide an application of the above-mentioned high heat-insulating and explosion-proof film, and to apply the above-mentioned film to car covers.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The high heat-insulating and explosion-proof film described in the present application, in the preparation of sol-gelled polyurethane, ultrasonic dispersion and addition of specific chemical substances are used to make the polyurethane form a stable sol state, thereby improving the compatibility of polyurethane with other raw materials and the overall performance of the film; by sol-gel treatment and coupling modification, a sol layer and a modified layer are formed on the surface of the hollow glass microspheres, thereby improving the impact resistance, heat insulation and bonding strength of the hollow glass microspheres with substrates such as polyurethane; in the present application, nanocellulose fibrils are used as reinforcing materials, and their high aspect ratio and excellent mechanical properties significantly improve the tensile strength and explosion-proof performance of the film.
[0034] The highly heat-insulating and explosion-proof film described in the present application is formed by using raw materials such as sol-gelled polyurethane, composite glass microsphere powder, nanocellulose fibrils, etc. under the action of a compatibilizer, a curing agent, and a dispersant to form a film with excellent heat-insulating, mechanical, and explosion-proof properties. DETAILED DESCRIPTION
[0035] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0036] As used herein, "and / or" includes the term of all combinations of any one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.
[0037] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.
[0038] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.
[0039] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0040] 50-60 parts of sol-gelled polyurethane, 5-10 parts of composite glass microsphere powder, 10-15 parts of compatibilizer, 1.0-1.5 parts of curing agent, 3-5 parts of nanocellulose fibrils, and 3-5 parts of dispersant;
[0041] The preparation method of the sol-formed polyurethane comprises the following steps:
[0042] Ammonia water and aqueous polyurethane are sequentially added to anhydrous ethanol, ultrasonically dispersed at room temperature, and then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane are added, stirred at room temperature for 5-6 hours, and then allowed to stand for 24-30 hours to obtain a sol-formed polyurethane;
[0043] The preparation method of the composite glass microsphere powder comprises the following steps:
[0044] Ammonia water and hollow glass microspheres are sequentially added to anhydrous ethanol, and ultrasonically dispersed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane are added to the suspension, stirred at room temperature for 8-9 hours, and then allowed to stand for 24-30 hours; and dried at 50-60° C. to obtain composite glass microsphere powder.
[0045] In some embodiments, the waterborne polyurethane is PU7104 waterborne polyurethane resin. The specific weight of the sol-formulated polyurethane can be any value among 50 parts, 51 parts, 55 parts, 57 parts, and 60 parts, within the range of 50-60 parts (including the endpoint values).
[0046] In some embodiments, the particle size of the hollow glass microspheres is 1-10 μm. The specific weight of the composite glass microsphere powder can be any value among 5 parts, 6 parts, 7 parts, 8 parts, and 10 parts, within the range of 5-10 parts (including the endpoint values).
[0047] In some embodiments, the nanocellulose fibrils have a diameter of 10-20 nm and a length of 100-200 nm. The specific weight of the nanocellulose fibrils can be any value among 3 parts, 4 parts, 4.5 parts, 4.8 parts, and 5 parts, within the range of 3-4 parts (including the end points).
[0048] In some embodiments, the compatibilizer is a maleic anhydride grafted compatibilizer. The specific weight of the compatibilizer can be any value of 10 parts, 11 parts, 12 parts, 13 parts, and 15 parts, within the range of 10-15 parts (including the endpoint value). The main function of the compatibilizer is to improve the compatibility between different polymers or polymers and fillers, thereby improving the overall performance of the composite material.
[0049] In some embodiments, the curing agent is diethylenetriamine or triethylenetetramine. The specific weight of the curing agent can be any value among 1 part, 1.1 parts, 1.2 parts, 1.3 parts, and 1.5 parts, and can be within the range of 1.0-1.5 parts (including the endpoint values).
[0050] In some embodiments, in the preparation method of the sol-gel polyurethane, the volume ratio of waterborne polyurethane, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:10-15:1;
[0051] In the preparation method of the composite glass microsphere powder, the feeding ratio of the hollow glass microsphere, tetraethyl silicate and dodecyltriethoxysilane is 1 g: (35-40) mL: (3-5) mL.
[0052] In some embodiments, the dispersant is sodium polyacrylate. The specific weight of the dispersant can be any value among 3 parts, 4 parts, 4.5 parts, 4.8 parts, and 5 parts, within the range of 3-4 parts (including the endpoint value). The dispersant is used to improve the dispersibility of the filler or pigment in the polymer substrate, ensure that the filler is evenly distributed in the film, thereby improving the uniformity and performance of the film.
[0053] The method for preparing the above-mentioned film comprises the following steps:
[0054] S1. Preparation of sol-gelled polyurethane
[0055] Ammonia water and aqueous polyurethane are sequentially added to anhydrous ethanol, ultrasonically dispersed at room temperature, and then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane are added, stirred at room temperature for 5-6 hours, and then allowed to stand for 24-30 hours to obtain a sol-formed polyurethane;
[0056] S2. Preparation of composite glass microsphere powder
[0057] Adding ammonia water and hollow glass microspheres to anhydrous ethanol in sequence, and performing ultrasonic dispersion at room temperature to obtain a suspension; adding tetraethyl silicate and dodecyltriethoxysilane to the suspension, stirring at room temperature for 8-9 hours, and then standing for 24-30 hours; drying at 50-60° C. to obtain composite glass microsphere powder;
[0058] S3. Preparation of mixed liquid
[0059] According to the weight composition of the high heat insulation and explosion-proof film, corresponding weight portions of raw materials are prepared; the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol are fully mixed; and then the sol-formed polyurethane and curing agent are added to obtain a mixed liquid;
[0060] S4. Film forming process
[0061] The mixed liquid is cast onto a PVC sheet; and dried at 40-60°C to obtain a highly heat-insulating and explosion-proof film.
[0062] In the embodiments and comparative examples, the sources of some raw materials are as follows:
[0063] Waterborne polyurethane: viscosity 50-500 mPa·S, solid content: 50±2%, PU7104 waterborne polyurethane resin from Shanghai Belt New Material Technology Co., Ltd.
[0064] Maleic anhydride grafted compatibilizer comes from Dongguan Xingyuan Chemical Co., Ltd.
[0065] Sodium polyacrylate CAS No.:9003-04-7.
[0066] Example 1
[0067] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0068] 50 parts of sol-gelled polyurethane, 5 parts of composite glass microsphere powder, 10 parts of maleic anhydride grafted compatibilizer, 1.0 part of diethylenetriamine, 3 parts of nanocellulose fibrils (diameter 10 nm, length 100 nm), and 3 parts of sodium polyacrylate;
[0069] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0070] S1. Preparation of sol-gelled polyurethane
[0071] Ammonia water (2 times the volume of PU7104 waterborne polyurethane resin) and PU7104 waterborne polyurethane resin were sequentially added to anhydrous ethanol (5 times the volume of PU7104 waterborne polyurethane resin), and ultrasonic dispersion was performed at room temperature. Then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane were added, and the mixture was stirred at room temperature for 5 hours, and then allowed to stand for 24 hours to obtain a sol-formed polyurethane.
[0072] The volume ratio of PU7104 waterborne polyurethane resin, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:10:1;
[0073] S2. Preparation of composite glass microsphere powder
[0074] Ammonia water (10 times the weight of the hollow glass microspheres) and hollow glass microspheres (particle size of 1 μm) were sequentially added to anhydrous ethanol (30 times the weight of the hollow glass microspheres), and ultrasonic dispersion was performed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane were added to the suspension, stirred at room temperature for 8 hours, and then allowed to stand for 24 hours; and dried at 50° C. to obtain composite glass microsphere powder;
[0075] The feeding ratio of hollow glass microspheres, tetraethyl silicate and dodecyltriethoxysilane is 1 g:35 mL:3 mL.
[0076] S3. Preparation of mixed liquid
[0077] According to the weight composition of the high heat-insulating explosion-proof film, prepare the corresponding weight portions of raw materials; fully mix the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of the solated polyurethane); then add the solated polyurethane and curing agent, and fully mix to obtain a mixed liquid;
[0078] S4. Film forming process
[0079] The mixed liquid is cast onto a PVC sheet and dried at 40°C to obtain a highly heat-insulating and explosion-proof film.
[0080] Example 2
[0081] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0082] 60 parts of sol-gelled polyurethane, 10 parts of composite glass microsphere powder, 15 parts of maleic anhydride grafted compatibilizer, 1.5 parts of diethylenetriamine, 5 parts of nanocellulose fibrils (diameter 20nm, length 200nm), and 5 parts of sodium polyacrylate;
[0083] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0084] S1. Preparation of sol-gelled polyurethane
[0085] Ammonia water (2 times the volume of PU7104 waterborne polyurethane resin) and PU7104 waterborne polyurethane resin were sequentially added to anhydrous ethanol (5 times the volume of PU7104 waterborne polyurethane resin), and ultrasonic dispersion was performed at room temperature. Then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane were added, and the mixture was stirred at room temperature for 6 hours, and then allowed to stand for 30 hours to obtain a sol-formed polyurethane.
[0086] The volume ratio of PU7104 waterborne polyurethane resin, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:15:1;
[0087] S2. Preparation of composite glass microsphere powder
[0088] Ammonia water (10 times the weight of the hollow glass microspheres) and hollow glass microspheres (particle size of 10 μm) were sequentially added to anhydrous ethanol (30 times the weight of the hollow glass microspheres), and ultrasonic dispersion was performed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane were added to the suspension, stirred at room temperature for 9 hours, and then allowed to stand for 30 hours; and dried at 60° C. to obtain composite glass microsphere powder;
[0089] The feeding ratio of hollow glass microspheres, tetraethyl silicate and dodecyltriethoxysilane is 1 g:40 mL:5 mL.
[0090] S3. Preparation of mixed liquid
[0091] According to the weight composition of the high heat-insulating explosion-proof film, prepare the corresponding weight portions of raw materials; fully mix the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of the solated polyurethane); then add the solated polyurethane and curing agent, and fully mix to obtain a mixed liquid;
[0092] S4. Film forming process
[0093] The mixed liquid is cast onto a PVC sheet and dried at 60°C to obtain a highly heat-insulating and explosion-proof film.
[0094] Example 3
[0095] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0096] 55 parts of sol-gelled polyurethane, 8 parts of composite glass microsphere powder, 12 parts of maleic anhydride grafted compatibilizer, 1.3 parts of diethylenetriamine, 4 parts of nanocellulose fibrils (diameter 15nm, length 150nm), and 4 parts of sodium polyacrylate;
[0097] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0098] S1. Preparation of sol-gelled polyurethane
[0099] Ammonia water (2 times the volume of PU7104 waterborne polyurethane resin) and PU7104 waterborne polyurethane resin were sequentially added to anhydrous ethanol (5 times the volume of PU7104 waterborne polyurethane resin), and ultrasonic dispersion was performed at room temperature. Then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane were added, and the mixture was stirred at room temperature for 5.5 hours, and then allowed to stand for 28 hours to obtain a sol-formed polyurethane.
[0100] The volume ratio of PU7104 waterborne polyurethane resin, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:13:1;
[0101] S2. Preparation of composite glass microsphere powder
[0102] Ammonia water (10 times the weight of the hollow glass microspheres) and hollow glass microspheres (particle size of 5 μm) were sequentially added to anhydrous ethanol (30 times the weight of the hollow glass microspheres), and ultrasonic dispersion was performed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane were added to the suspension, stirred at room temperature for 8.5 hours, and then allowed to stand for 27 hours; and dried at 55° C. to obtain composite glass microsphere powder;
[0103] The feeding ratio of hollow glass microspheres, tetraethyl silicate and dodecyltriethoxysilane is 1 g: 38 mL: 4 mL.
[0104] S3. Preparation of mixed liquid
[0105] According to the weight composition of the high heat-insulating explosion-proof film, prepare the corresponding weight portions of raw materials; fully mix the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of the solated polyurethane); then add the solated polyurethane and curing agent, and fully mix to obtain a mixed liquid;
[0106] S4. Film forming process
[0107] The mixed liquid is cast onto a PVC sheet and dried at 50°C to obtain a highly heat-insulating and explosion-proof film.
[0108] Example 4
[0109] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0110] 51 parts of sol-gelled polyurethane, 6 parts of composite glass microsphere powder, 11 parts of maleic anhydride grafted compatibilizer, 1.1 parts of triethylenetetramine, 3 parts of nanocellulose fibrils (diameter 12nm, length 120nm), 4 parts of sodium polyacrylate;
[0111] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0112] S1. Preparation of sol-gelled polyurethane
[0113] Ammonia water (2 times the volume of PU7104 waterborne polyurethane resin) and PU7104 waterborne polyurethane resin were sequentially added to anhydrous ethanol (5 times the volume of PU7104 waterborne polyurethane resin), and ultrasonic dispersion was performed at room temperature. Then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane were added, and the mixture was stirred at room temperature for 5 hours, and then allowed to stand for 25 hours to obtain a sol-formed polyurethane.
[0114] The volume ratio of PU7104 waterborne polyurethane resin, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:11:1;
[0115] S2. Preparation of composite glass microsphere powder
[0116] Ammonia water (10 times the weight of the hollow glass microspheres) and hollow glass microspheres (particle size of 7 μm) were sequentially added to anhydrous ethanol (30 times the weight of the hollow glass microspheres), and ultrasonic dispersion was performed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane were added to the suspension, stirred at room temperature for 8 hours, and then allowed to stand for 25 hours; and dried at 52° C. to obtain composite glass microsphere powder;
[0117] The feeding ratio of hollow glass microspheres, tetraethyl silicate and dodecyltriethoxysilane is 1 g:36 mL:3 mL.
[0118] S3. Preparation of mixed liquid
[0119] According to the weight composition of the high heat-insulating explosion-proof film, prepare the corresponding weight portions of raw materials; fully mix the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of the solated polyurethane); then add the solated polyurethane and curing agent, and fully mix to obtain a mixed liquid;
[0120] S4. Film forming process
[0121] The mixed liquid is cast onto a PVC sheet and dried at 45°C to obtain a highly heat-insulating and explosion-proof film.
[0122] Example 5
[0123] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0124] 58 parts of sol-gelled polyurethane, 9 parts of composite glass microsphere powder, 14 parts of maleic anhydride grafted compatibilizer, 1.4 parts of triethylenetetramine, 4 parts of nanocellulose fibrils (diameter 18nm, length 180nm), 5 parts of sodium polyacrylate;
[0125] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0126] S1. Preparation of sol-gelled polyurethane
[0127] Ammonia water (2 times the volume of PU7104 waterborne polyurethane resin) and PU7104 waterborne polyurethane resin were sequentially added to anhydrous ethanol (5 times the volume of PU7104 waterborne polyurethane resin), and ultrasonic dispersion was performed at room temperature. Then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane were added, and the mixture was stirred at room temperature for 6 hours, and then allowed to stand for 27 hours to obtain a sol-formed polyurethane.
[0128] The volume ratio of PU7104 waterborne polyurethane resin, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:14:1;
[0129] S2. Preparation of composite glass microsphere powder
[0130] Ammonia water (10 times the weight of the hollow glass microspheres) and hollow glass microspheres (particle size of 8 μm) were sequentially added to anhydrous ethanol (30 times the weight of the hollow glass microspheres), and ultrasonic dispersion was performed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane were added to the suspension, stirred at room temperature for 8.5 hours, and then allowed to stand for 28 hours; and dried at 58° C. to obtain composite glass microsphere powder;
[0131] The feeding ratio of hollow glass microspheres, tetraethyl silicate and dodecyltriethoxysilane is 1 g:37 mL:5 mL.
[0132] S3. Preparation of mixed liquid
[0133] According to the weight composition of the high heat-insulating explosion-proof film, prepare the corresponding weight portions of raw materials; fully mix the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of the solated polyurethane); then add the solated polyurethane and curing agent, and fully mix to obtain a mixed liquid;
[0134] S4. Film forming process
[0135] The mixed liquid is cast onto a PVC sheet and dried at 55°C to obtain a highly heat-insulating and explosion-proof film.
[0136] Comparative Example 1
[0137] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0138] 50 parts of PU7104 waterborne polyurethane resin, 5 parts of composite glass microsphere powder, 10 parts of maleic anhydride grafted compatibilizer, 1.0 part of diethylenetriamine, 3 parts of nanocellulose fibrils (diameter 10nm, length 100nm), 3 parts of sodium polyacrylate;
[0139] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0140] S1. Preparation of composite glass microsphere powder
[0141] Ammonia water (10 times the weight of the hollow glass microspheres) and hollow glass microspheres (particle size of 1 μm) were sequentially added to anhydrous ethanol (30 times the weight of the hollow glass microspheres), and ultrasonic dispersion was performed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane were added to the suspension, stirred at room temperature for 8 hours, and then allowed to stand for 24 hours; and dried at 50° C. to obtain composite glass microsphere powder;
[0142] The feeding ratio of hollow glass microspheres, tetraethyl silicate and dodecyltriethoxysilane is 1 g:35 mL:3 mL.
[0143] S2. Preparation of mixed liquid
[0144] Prepare the raw materials in corresponding weight parts according to the weight composition of the high heat-insulating explosion-proof film; fully mix the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of PU7104 water-based polyurethane resin); then add PU7104 water-based polyurethane resin and curing agent, and fully mix to obtain a mixed liquid;
[0145] S3. Film forming process
[0146] The mixed liquid is cast onto a PVC sheet and dried at 40°C to obtain a highly heat-insulating and explosion-proof film.
[0147] Comparative Example 2
[0148] A highly heat-insulating and explosion-proof film comprises the following raw materials in parts by weight:
[0149] 50 parts of sol-gelled polyurethane, 5 parts of hollow glass microspheres (particle size 1 μm), 10 parts of maleic anhydride grafted compatibilizer, 1.0 part of diethylenetriamine, 3 parts of nanocellulose fibrils (diameter 10 nm, length 100 nm), and 3 parts of sodium polyacrylate;
[0150] The method for preparing a highly heat-insulating and explosion-proof film comprises the following steps:
[0151] S1. Preparation of sol-gelled polyurethane
[0152] Ammonia water (2 times the volume of PU7104 waterborne polyurethane resin) and PU7104 waterborne polyurethane resin were sequentially added to anhydrous ethanol (5 times the volume of PU7104 waterborne polyurethane resin), and ultrasonic dispersion was performed at room temperature. Then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane were added, and the mixture was stirred at room temperature for 5 hours, and then allowed to stand for 24 hours to obtain a sol-formed polyurethane.
[0153] The volume ratio of PU7104 waterborne polyurethane resin, tetraethyl silicate, and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:10:1;
[0154] S2. Preparation of mixed liquid
[0155] According to the weight composition of the high heat-insulating explosion-proof film, prepare the corresponding weight portions of raw materials; fully mix the hollow glass microspheres, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol (the added volume of anhydrous ethanol is 5 times the volume of the solated polyurethane); then add the solated polyurethane and curing agent, and fully mix to obtain a mixed liquid;
[0156] S3. Film forming process
[0157] The mixed liquid is cast onto a PVC sheet and dried at 40°C to obtain a highly heat-insulating and explosion-proof film.
[0158] Comparative Example 3
[0159] A highly heat-insulating and explosion-proof film, wherein no nanocellulose fibrils are added to the raw materials, and other conditions are consistent with those in the embodiment.
[0160] The films prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to the following performance tests:
[0161] 1. Thermal insulation effect test
[0162] A self-made incubator was used for the test. The surrounding and bottom of the incubator were foam insulation layers, and the upper part was ordinary quartz glass with a film prepared in Examples 1-5 and Comparative Examples 1-3 attached thereto. The size was 50cmx20cmx20cm. The temperature probe of the thermocouple thermometer of the intelligent inspection instrument was located in the center of the box, and a baffle was used to prevent direct light. The lighting source was a 250W infrared lamp with an irradiation distance of 25cm. The temperature differences inside and outside the incubator at 20min, 40min and 60min were measured and calculated respectively.
[0163] 2. Explosion-proof performance test
[0164] On an ordinary glassware with a specification of 10cm×5cm×5cm, a film prepared in Examples 1-5 and Comparative Examples 1-3 with a thickness of 2mm was attached, and a blank example (without film attached) was also set up; the above glassware was impacted with an explosion shock wave of 0.05MPa, and the damage of each glassware was observed.
[0165] 3. Tensile strength
[0166] It was carried out according to ASTM-D638.
[0167] The above test results are summarized in Table 1 below;
[0168] Table 1
[0169]
[0170] As can be seen from Table 1, the temperature difference between the inside and outside of the insulation box of Examples 1-5 (i.e., the films of the present invention) at 20 minutes, 40 minutes, and 60 minutes is significantly higher than that of Comparative Examples 1-2 and Comparative Example 3 (i.e., the film raw material formula of the present invention is not used or the complete raw material formula of the present invention is not used), which indicates that the film of the present invention has better thermal insulation performance.
[0171] The damage of the glass in Examples 1-5 was "no change", which shows that the film can effectively prevent the glass from breaking and shows excellent explosion-proof performance. Comparative Example 1 showed "slight cracks", Comparative Example 2 showed "more cracks", Comparative Example 3 showed "slight breakage", and the blank glass (without film attached) showed "obvious breakage", which further illustrates the explosion-proof effect of the film of the present invention.
[0172] The tensile strengths of Examples 1-5 are all above 38 MPa, which are significantly higher than 30 MPa of Comparative Example 1, 21 MPa of Comparative Example 2, and 15 MPa of Comparative Example 3, indicating that the film of the present invention has higher mechanical strength.
[0173] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A highly heat-insulating and explosion-proof film, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of sol-gelled polyurethane, 5-10 parts of composite glass microsphere powder, 10-15 parts of compatibilizer, 1.0-1.5 parts of curing agent, 3-5 parts of nanocellulose fibrils, and 3-5 parts of dispersant; The preparation method of the sol-formed polyurethane comprises the following steps: Ammonia water and aqueous polyurethane are sequentially added to anhydrous ethanol, ultrasonically dispersed at room temperature, and then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane are added, stirred at room temperature for 5-6 hours, and then allowed to stand for 24-30 hours to obtain a sol-formed polyurethane; The preparation method of the composite glass microsphere powder comprises the following steps: Ammonia water and hollow glass microspheres are sequentially added to anhydrous ethanol, and ultrasonically dispersed at room temperature to obtain a suspension; tetraethyl silicate and dodecyltriethoxysilane are added to the suspension, stirred at room temperature for 8-9 hours, and then allowed to stand for 24-30 hours; and dried at 50-60° C. to obtain composite glass microsphere powder.
2. The film according to claim 1, characterized in that The aqueous polyurethane has a viscosity of 50-500 mPa·S.
3. The film according to claim 1, characterized in that The particle size of the hollow glass microspheres is 1-10 μm.
4. The film according to claim 1, characterized in that The nanocellulose fibrils have a diameter of 10 to 20 nm and a length of 100 to 200 nm.
5. The film according to claim 1, characterized in that The compatibilizer is a maleic anhydride grafted compatibilizer.
6. The film according to claim 1, characterized in that The curing agent is diethylenetriamine or triethylenetetramine.
7. The film according to claim 1, characterized in that In the preparation method of the sol-formed polyurethane, the volume ratio of waterborne polyurethane, tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane is 1:10-15:1; In the preparation method of composite glass microsphere powder, hollow glass microspheres, tetraethyl silicate, The feed ratio of dodecyltriethoxysilane = 1 g: (35-40) mL: (3-5) mL.
8. The film according to claim 1, characterized in that The dispersant is sodium polyacrylate.
9. The method for preparing a thin film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of sol-gelled polyurethane Ammonia water and aqueous polyurethane are sequentially added to anhydrous ethanol, ultrasonically dispersed at room temperature, and then tetraethyl silicate and 1H,1H,2H,2H-perfluorooctyltrichlorosilane are added, stirred at room temperature for 5-6 hours, and then allowed to stand for 24-30 hours to obtain a sol-formed polyurethane; S2. Preparation of composite glass microsphere powder Adding ammonia water and hollow glass microspheres to anhydrous ethanol in sequence, and performing ultrasonic dispersion at room temperature to obtain a suspension; adding tetraethyl silicate and dodecyltriethoxysilane to the suspension, stirring at room temperature for 8-9 hours, and then standing for 24-30 hours; drying at 50-60° C. to obtain composite glass microsphere powder; S3. Preparation of mixed liquid According to the weight composition of the high heat insulation and explosion-proof film, corresponding weight portions of raw materials are prepared; the composite glass microsphere powder, dispersant, compatibilizer, nanocellulose fibrils, and anhydrous ethanol are fully mixed; and then the sol-formed polyurethane and curing agent are added to obtain a mixed liquid; S4. Film forming process The mixed liquid is cast onto a PVC sheet; and dried at 40-60°C to obtain a highly heat-insulating and explosion-proof film.
10. Application of a high heat-insulating explosion-proof film, characterized in that: The film described in any one of claims 1 to 8 or the film prepared by the preparation method described in claim 9 is applied to a car cover.
